The political economy of enforcer liability for wrongful police stops. (27th August 2020) - Friehe, Tim; Mungan, Murat C.
Abstract: This article questions whether excessive policing practices can persist in an environment where law enforcement policies are subject to political pressures. Specifically, it considers a setting where the police decide whether to conduct stops based on the suspiciousness of a person's behavior and the potential liability for conducting a wrongful stop. We establish that the liability level that results in a voting equilibrium is smaller than optimal, and consequently, that excessive policing practices emerge in equilibrium.